2017
DOI: 10.1016/j.cortex.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Tau, amyloid, and cascading network failure across the Alzheimer's disease spectrum

Abstract: Functionally related brain regions are selectively vulnerable to Alzheimer’s disease pathophysiology. However, molecular markers of this pathophysiology (i.e., beta-amyloid and tau aggregates) have discrepant spatial and temporal patterns of progression within these selectively vulnerable brain regions. Existing reductionist pathophysiologic models cannot account for these large-scale spatiotemporal inconsistencies. Within the framework of the recently proposed cascading network failure model of Alzheimer’s di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
194
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 197 publications
(245 citation statements)
references
References 66 publications
27
194
1
Order By: Relevance
“…Studies have suggested that the regional pattern of Aβ deposition is consistent across clinical phenotypes of AD and is not related to neurodegeneration (Bischof et al, 2016; Iaccarino et al, 2018; La Joie et al, 2012; Ossenkoppele et al, 2015; Ossenkoppele et al, 2016; Rabinovici et al, 2008), while tau topographically matches grey matter atrophy and glucose hypometabolism and can therefore be interpreted as the likely driving force behind neurodegeneration (Dronse et al, 2017; Ossenkoppele et al, 2016; Jennifer L Whitwell et al, 2018; Xia et al, 2017). Additionally, it has been observed that AD pathological proteins may spread along functional brain networks, with strongly connected regions displaying a higher tau burden (Cope et al, 2018; Hoenig et al, 2018; Jones et al, 2017) and amyloid being a partial mediator between functional network failure and tau deposition (Jones et al, 2017). The majority of these studies have assessed the spectrum of AD clinical presentations, including both typical and atypical variants.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that the regional pattern of Aβ deposition is consistent across clinical phenotypes of AD and is not related to neurodegeneration (Bischof et al, 2016; Iaccarino et al, 2018; La Joie et al, 2012; Ossenkoppele et al, 2015; Ossenkoppele et al, 2016; Rabinovici et al, 2008), while tau topographically matches grey matter atrophy and glucose hypometabolism and can therefore be interpreted as the likely driving force behind neurodegeneration (Dronse et al, 2017; Ossenkoppele et al, 2016; Jennifer L Whitwell et al, 2018; Xia et al, 2017). Additionally, it has been observed that AD pathological proteins may spread along functional brain networks, with strongly connected regions displaying a higher tau burden (Cope et al, 2018; Hoenig et al, 2018; Jones et al, 2017) and amyloid being a partial mediator between functional network failure and tau deposition (Jones et al, 2017). The majority of these studies have assessed the spectrum of AD clinical presentations, including both typical and atypical variants.…”
Section: Introductionmentioning
confidence: 99%
“…Aβ disrupts synaptic functioning, resulting in aberrant brain connectivity at the synaptic level (Selkoe, 2002; Spires‐Jones & Hyman, 2014), as well as on the whole‐brain connectivity level (Delbeuck, der Linden, & Collette, 2003; Hedden et al., 2009). Although the precise sequence of events caused by Aβ plaques is still being investigated (Altmann, Ng, Landau, Jagust, & Greicius, 2015) and interactions with other agents recognized (Jones et al., 2017), the key role of Aβ in AD pathology is beyond doubt (Jack et al., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The improvement observed is likely due to the data-driven nature of the method used for derivation of the clusters. 47 .…”
Section: Cc-by-nc-ndmentioning
confidence: 99%